What Influence Employees’ Intention to Join a Union? / Nurul Arissa Mohamad Yusuf, Nur Azreena Othman and Mahazril ‘Aini Yaacob - Mohamad Yusuf, Nurul Arissa; Othman, Nur Azreena; Yaacob, Mahazril ‘Aini (2021)
The trade union is one of the independent organisations that play a crucial role in protecting employment rights and interests. Employee rights include terms and conditions of employment, such as wages, welfare, and security matters. Hodder and Edwards (2015) defined a trade union as an independent organisation created by workers to achieve common objectives such as better job benefits. Their roles including maintaining and improving employment conditions, environments, and conditions and exercise their rights to achieve employee goals and needs (Bushiri, 2014). In Malaysia, trade unions play a function that important in the industrial relations agenda involving mutual relations between employers and employees. Issues related to employees' welfare and rights have been the common interest of much foreign research aiming to understand trade unions' effectiveness (Goerke, 2020; Yao, 2013; Shresta, 2012; Moeti-Lysson & Ongori, 2011). In the context of Malaysia, previous research have focused on government policies regarding the trade unions (Mahadirin Ahmad, Sabariah Kee Mohd Yussof & Nor Syakirah Zakaria, 2019), employers and employees attitude and perception on union effectiveness (Tarumaraja, Fatimah Wati Halim & Fatimah Omar, 2017; Hazrul Shahiri, Zulkifly Osman & Park, 2016; Raduan Che Rose, Kumar & Ramasamy, 2011), women in trade unions (Rohana Ariffin, 2007; Crinis, 2003), trade union growth (Fatimah Said, Roza Hazli Zakaria & Saad Mohd. Said, 2002) and trade union leadership during world economy crisis (Che Wan Takwa Che Wan Abu Bakar, 2008). However, Malaysian trade union membership experienced a small growth percentage over seven years. Based on the Department of Union Affairs (2019), the number of union membership as of July 2019 was only at 930,790, with only 759 registered trade unions in Malaysia. The Starbucks Workers Union is a trade union formed by members of the Industrial Workers of the World (IWW). In a larger context, trade unions serve as an institution to balance the employer's power and government power. Employees join unions out of a desire to be represented. Employees believe that unions can improve their economy or well-being by increasing wages and better benefit facilities. The employee also believes that unions can protect them from discriminatory and unfair treatment by management. Therefore, the study aims to know how many employees join a union and what factors influence their intention to join it.